2014
DOI: 10.1007/978-3-662-43862-6_12
|View full text |Cite
|
Sign up to set email alerts
|

A Study of RPL DODAG Version Attacks

Abstract: Abstract. The IETF designed the Routing Protocol for Low power and Lossy Networks (RPL) as a candidate for use in constrained networks. Keeping in mind the different requirements of such networks, the protocol was designed to support multiple routing topologies, called DODAGs, constructed using different objective functions, so as to optimize routing based on divergent metrics. A DODAG versioning system is incorporated into RPL in order to ensure that the topology does not become stale and that loops are not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…A probabilistic attacker model is incorporated here. Based on the simulations, in addition to the location-effect correlation found in Mayzaud's work [35], the authors found out that the mobile attackers' Mobile attackers are more detrimental and attack triples the power consumption of the network effect can be as detrimental as the farthest attacking position in the network. They also showed that, version number attacks can increase the power consumption of the nodes by more than a factor of two.…”
Section: Studies That Analyze D/dos Attacks For Internet Of Thingsmentioning
confidence: 93%
See 2 more Smart Citations
“…A probabilistic attacker model is incorporated here. Based on the simulations, in addition to the location-effect correlation found in Mayzaud's work [35], the authors found out that the mobile attackers' Mobile attackers are more detrimental and attack triples the power consumption of the network effect can be as detrimental as the farthest attacking position in the network. They also showed that, version number attacks can increase the power consumption of the nodes by more than a factor of two.…”
Section: Studies That Analyze D/dos Attacks For Internet Of Thingsmentioning
confidence: 93%
“…However, there is no mechanism in RPL which guarantees that only the DODAG root can change the version number field. Malicious nodes can change the version number and force the entire network to set up the DODAG from scratch [11,35]. This attack is called Version Number attack and it affects the network with unnecessary control messages, delays, packet losses and reduced network lifetime.…”
Section: D/dos Attacks To the Network Layermentioning
confidence: 99%
See 1 more Smart Citation
“…It then attempts to attract a child node for selection as a parent or improves some other metric and attracts significant traffic directed toward the root. Only minimal research was proposed to describe and mitigate the version number attack in Refs [13,16]. Some of these attempt to address the attack by using a mechanism; others merely describe the attacks.…”
Section: Related Workmentioning
confidence: 99%
“…From the other side, the adversary can exploit the functioning rules of RPL to trigger specification-based attacks (i.e. Version number attack [7] [8], Rank attacks [9] [8], DIS attack [9], DAO attacks [10] [11], Local repair attack [12] [13], etc.). Both gaps can be combined and exploited by a Sybil node to disturb RPL.…”
Section: Introductionmentioning
confidence: 99%